Factors Affecting Deposit Mobilization of Commercial Bank in Nepal - Khanal, Parbati (INTELLIGENCE Journal of Multidisciplinary Research, 2026)
Deposit Mobilization is a fundamental function of commercial banks that supports financial intermediation promotes capital formation and contributes to national economic growth. This study was done to investigates the factors affecting deposit mobilization among commercial banks in Nepal over a ten-year period (FY 2012/13-2021/22). A descriptive and analytical research design was adopted for the study. The total population comprised 20 commercial banks operating in Nepal (Nepal Rastra Bank, 2023). Among them, a sample of 12 major commercial banks was selected using purposive sampling techniques, ensuring representing different ownership and operational categories. Primary data were collected through structured questionnaires distributed to bank officials and employees in the same banks to capture qualitative insights regarding deposit mobilization strategies. This study utilized secondary data obtained from annual reports of the selected banks, publications of Nepal Rastra Banks, and data. From the world Bank. Descriptive statistics ratio analysis, correlation and regression model were applied to examine the relationship between deposit mobilization and its determinants; return on assets (ROA), loan to deposit ratio (LTD), capital adequacy (CA), inflation (INF) and gross domestic product (GDP). The Findings revealed to ROA, LTD, CA have a positive but statistically insignificant impact on deposit mobilization, whereas macroeconomic variables such as inflation and GDP exert a significant negative influence. These results suggest that internal financial performance indicators alone are insufficient to enhance deposit growth without stable macroeconomic conditions. Therefore, policies promoting low inflation, sustainable economic growth, and strengthened banking confidence are crucial for improving deposit mobilization and ensuring financial stability in Nepal. The findings of this study have important implication for policymakers, banking institutions, and regulators such as the Nepal Rastra Bank.